The role of measuring sustainable manufacturing costs using the accelerated implementation method in reducing costs (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Sustainable manufacturing is one of the approaches adopted by the construction industry to achieve sustainability and implement environmentally friendly construction projects. Therefore, the use of sustainable manufacturing in the construction industry has become a vital requirement in modern environmental practices, as it contributes to high levels of environmental protection and reduces the adverse effects of pollution. Fast-track construction is one of the methods used to reduce construction project timelines in terms of time and cost, leading to more efficient project delivery compared to traditional methods. This research aims to present the knowledge foundations of sustainable manufacturing and fast-track construction, in addition to developing a mechanism for cost reduction in the construction industry by setting plans to control time and cost factors, based on the operational mechanisms of fast-track construction to measure the costs of sustainable manufacturing in a project. To achieve this, the study adopted a descriptive methodology for the theoretical part, relying on books, theses, dissertations, and both Arabic and international articles related to the research topic. The practical part of the research focused on measuring the costs of sustainable manufacturing using the fast-track method to reduce expenses when applied to the Iraq Gate project, relying on financial data and personal interviews with engineers and workers. The study reached a number of conclusions, the most important of which is that the costs of sustainable manufacturing, when using fast-track construction, contribute to reducing both costs and project completion time compared to traditional methods. It also reduces the use of natural resources, making them more sustainable, and limits emissions and gases generated by the project. Furthermore, the costs of sustainable manufacturing provide a comprehensive view of the use of materials and energy throughout the project’s implementation stages, achieving a balance between environmental, economic, and social indicators. The research also presented several recommendations, most notably the need to adopt sustainable manufacturing costs through fast-track construction in order to reduce construction industry expenses.